2012
DOI: 10.1159/000343784
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Differences in Vitamin D Levels in Children and Adolescents and Their Relation to Endurance Performance

Abstract: Aims: The present study investigated whether sociodemographic factors and physical activity (PA) are associated with differences in serum 25-hydroxyvitamin D [25(OH)D] levels and whether these differences are associated with varying levels of endurance performance and body mass index (BMI) in children and adolescents. Subjects and Methods: Path analyses were based on data of a nationwide, cross-sectional German Health Interview and Examination Survey for Children (KiGGS; 2003 until 2006) for 25(OH)D and the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 92 publications
2
3
1
Order By: Relevance
“…This finding is supported by an early study which reported increased aerobic capacity as a result of exposure to ultraviolet radiation in collegiate students [8]. Furthermore, a recent study on adolescents observed a positive relationship between vitamin D and aerobic performance on adolescents [38] Since VO 2 max is related to soccer performance, as indicated by the well-documented relationship between this parameter and the distance covered during a soccer game [15], our findings suggest that in order to perform efficiently during a soccer game optimal vitamin D levels are needed. The observed association between vitamin D levels and VO 2 max could be related to its protective effect on lung function.…”
Section: Discussionsupporting
confidence: 63%
“…This finding is supported by an early study which reported increased aerobic capacity as a result of exposure to ultraviolet radiation in collegiate students [8]. Furthermore, a recent study on adolescents observed a positive relationship between vitamin D and aerobic performance on adolescents [38] Since VO 2 max is related to soccer performance, as indicated by the well-documented relationship between this parameter and the distance covered during a soccer game [15], our findings suggest that in order to perform efficiently during a soccer game optimal vitamin D levels are needed. The observed association between vitamin D levels and VO 2 max could be related to its protective effect on lung function.…”
Section: Discussionsupporting
confidence: 63%
“…It is challenging to measure vitamin D status as the obtained concentrations vary with the methods applied 28 . In GINIplus and LISAplus the measured 25(OH)D levels were higher than reported for this age group in the KIGGS study 29 and NHANES 30 . Therefore, we used in our analyses 25(OH)D concentrations as continuous variable as well as in quartiles and avoided interpretation in terms of vitamin D sufficiency.…”
Section: Discussioncontrasting
confidence: 62%
“…In brief, in a German study, PA was not correlated with 25(OH)D status in 11- to 13-year-old children [ 29 ], which is consistent with the results of a Danish study that observed eight- to 11-year-old children [ 28 ]. In contrast, another Danish study reported a positive association between PA and 25(OH)D status in younger children (aged 4–8 years) [ 16 ], and similar correlations and potentially positive effects of increased PA on 25(OH)D status were observed in children and adolescents from other world regions [ 9 , 17 , 30 , 31 ].…”
Section: Introductionsupporting
confidence: 84%
“…Recent years have seen an increase in public interest in the relationship between PA and 25(OH)D status in children, mostly because studies completed over the last decade have regularly confirmed a high prevalence of 25(OH)D deficiency in children and adolescents [ 9 , 27 ]. However, the results of studies that specifically investigated a possible correlation between PA and 25(OH)D status in children are not consistent [ 16 , 17 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%